2016
DOI: 10.1590/1518-8345.1187.2798
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis control in people living with HIV/AIDS

Abstract: Objective: to analyze the offering of health actions and services for the control of tuberculosis for people living with HIV/AIDS being followed up in the Specialized Care Services for HIV/AIDS in Ribeirão Preto, SP, Brazil. Method: quantitative, exploratory survey study. Participated 253 people living with HIV/AIDS followed up by this service, considering as inclusion criteria: individuals older than 18 years living in the city and not inmates. Data collection was conducted from January 2012 to May 2013 throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 21 publications
1
15
0
8
Order By: Relevance
“…However, factors such as male gender, economically active age, active employment status, recurrence and re-treatment of TB, pulmonary clinical form of TB, presence of comorbidities, use of drugs and alcohol, and irregular ART withdrawal. (14,15,22,27,29,39) This result prompts reflections on data quality of information systems used in this study and the truthfulness of the self-reported information. In this sense, it is believed that there may be an information bias due to secondary data sources use consulted for the study development.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…However, factors such as male gender, economically active age, active employment status, recurrence and re-treatment of TB, pulmonary clinical form of TB, presence of comorbidities, use of drugs and alcohol, and irregular ART withdrawal. (14,15,22,27,29,39) This result prompts reflections on data quality of information systems used in this study and the truthfulness of the self-reported information. In this sense, it is believed that there may be an information bias due to secondary data sources use consulted for the study development.…”
Section: Discussionsupporting
confidence: 57%
“…TB involvement also shows the marginalization and predominance of cases in the most disadvantaged segments of society, (27) reinforcing the social character linked to the disease. (14) As for skin color, most of individuals were white, which also occurred in other investigations focusing on TB.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Embora a maioria dos casos notificados tenham feito o teste para HIV, é importante salientar que pessoas infectadas por HIV estão de 21 a 34 vezes mais propensas a desenvolver TB quando comparadas a população geral, sendo esta, a principal causa de morte por doença infecciosa em pessoas com HIV. Devido à resposta imunológica deficiente, pessoas que vivem com o vírus HIV, possuem maior risco de reativação da doença podendo aumentar o risco de transmissão do bacilo da TB para a população geral 28,29 . Em relação a situação de encerramento, os índices encontrados não estão de acordo com o preconizado pela OMS 1 [30][31][32] .…”
Section: Discussionunclassified
“…4 In 2012, the health care network of the municipality was structured in five Health Districts, having 42 serviços de of Primary Health Care (Primary Health Care Unit-PHC and Family Health Unit-FHU), five units of Secondary/ Tertiary Care (District Health Units -DHU) that assist diverse spacialities and four of them offered emergency room (ER), an emergency care unit (ECU) and three hospitals. 14 With regard to the diagnosis of HIV/aids, all the health units of the public network of the municipality (PHC, DHU, ER e Hospitals) could ask for an anti-HIV exam and in case of positive diagnosis, the individual was sent to one of SCS of the municipality, which was distributed in five health districts and operated with specialized teams, providing services such as Home Care Service (HCS) and Testing and Counseling Centers (TCC). Five TCC of the municipality offered Quick Diagnosis Test for HIV with result emission in 30 minutes.…”
Section: Methodsmentioning
confidence: 99%